Orchard’s Pruning for Energy Purposes – Methodology of Environmental Impact Assessment of New Logistic Chain Developed within Europruning Project – Part 2 (Agricultural Engineering, 2018)
To determine the environmental impact, the assessment of the Euro-Pruning project strategy has been carried out in accordance with the checking and scooping list related to Directive 97/11/EC. Additionally, some suggestions and recommendations to prevent/minimize the hazard of accidents or negative interaction on surrounding have been elaborated (according to the suggested procedure in ISO 14001 methodology: risk definition and prevention action proposal). As a consequence, the results of the inspection during the demo tests taking place in different orchards/plantations regarding the performance of the machineries operation, farmers’ habits and pruning residues harvesting procedures have been presented, in order to diagnose and determine possible risks that may occur and influence negatively the local environment. Similar activities have been carried out during the storage tests and transportation processes.